Artistic Research: A Vibrant and Ever-Changing Field - Tomlinson, Vanessa (Performance Matters, 2023)
This article looks at artistic research from an Australian perspective, with an emphasis on the role professional doctorates have played in developing this field. In 2017, I co-wrote "Two Decades of Artistic Research: The Antipodal Experience," which examined the state of artistic research in Australia at that time. Six years later, revisiting this body of work, I am reminded of how important the training of doctoral candidates is to the expansion and maturation of artistic research. In this writing, I share some best practice theses from the discipline of music, and share some of the tensions and successes in how universities measure creative research output.